THE USE OF CANVA-BASED LEARNING ANIMATION MEDIA IN GRADE V SCIENCE SUBJECTS IN ELEMENTARY SCHOOLS - Fadhlia, Anisa; Prastowo, Andi (PIONIR: JURNAL PENDIDIKAN, 2024)
This study aims to see how the learning process occurs using Canva-based animation media in science learning at SD IT Al-Fatih Peusangan. The subjects in this study were class teachers and class V students. Qualitative research is research that produces descriptive information in the form of written and spoken words. Data collection techniques are by interviews via mobile phones and filling in google from. The results of the study show that by using animation media, students like and feel happy because they can easily understand the material, learning, and also learning becomes more interesting. The difficulty of teachers in using animation media is the lack of projectors, LCDs, internet in schools and the difficulty of choosing characters when creating animation media.Keywords: IPAS, Information technology, canva-based animation media